Order of growth of solutions to algebraic differential equations in the unit disk - D. Benbourenane; L. R. Sons (International Journal of Mathematics and Mathematical Sciences)
S. B. Bank has shown that there is no uniform growth estimate for meromorphic solutions of algebraic differential equations with meromorphic coefficients in the unit disk. We give conditions under which such solutions must have a finite order of growth.